भोपाल जिले के शिक्षक शिक्षा महाविद्यालयों में कार्यरत शिक्षकों में दायित्व बोध एवं नवाचार के प्रति जागरूकता का अध्ययन. (A Study on the Sense of Responsibility and Awareness Towards Innovation among Teachers in Teacher Education Colleges in Bhopal District) - Sahu, Pushp Lata (Innovare Journal of Education, 2024)
प्रस्तुत अध्ययन का उद्देश्य भोपाल जिले में स्थित राष्ट्रीय अध्यापक परिषद द्वारा वर्ष 2024 में संचालित शिक्षक शिक्षा महाविद्यालयों में कार्यरत शिक्षकों में दायित्व बोध एवं नवाचार के प्रति जागरूकता का अध्ययन करना था। जिसके लिए चार उद्देश्यों का निर्माण किया गया उन उद्देश्यों की पूर्ति के लिए शोधार्थी ने कल 150 उत्तरदाताओं का चयन संभाव्य न्यादर्श विधि द्वारा किया। जिनमें से 100 महिलाएं एवं 50 पुरुषों का चयन उत्तरदाताओं के रूप में किया, और 20 प्रश्नों की एक प्रश्नावली का निर्माण आंकड़ों के संकलन के लिए किया। अध्ययन में यह पाया गया कि जिन शिक्षकों में अपने दायित्वों के प्रति सजगता अधिक थी, वे अपने शिक्षण में नवाचार अपनाने के प्रति अधिक इच्छुक थे। शोध से यह भी स्पष्ट हुआ कि सीमित संसाधन नवाचारों को पूरी तरह अपनाने में बाधक हैं, लेकिन शिक्षकों ने डिजिटल तकनीक और सक्रिय शिक्षण विधियों को अपने शिक्षण में शामिल करने की आवश्यकता को पहचाना। निष्कर्षों से यह संकेत मिलता है कि शिक्षकों की जिम्मेदारी और नवाचार आपस में गहराई से जुड़े हुए हैं और इनका प्रभाव शिक्षण की गुणवत्ता और छात्रों की सहभागिता पर पड़ता है। The purpose of the present study was to examine the sense of responsibility and awareness toward innovation among teachers working in teacher education colleges operated by the National Council for Teacher Education in the Bhopal district in the year 2024. For this, four objectives were formulated, and to fulfill those objectives, the researcher selected 150 respondents through the probable sampling method. Among them, 100 women and 50 men were chosen as respondents, and a questionnaire of 20 questions was developed for data collection. The study found that teachers who were more aware of their responsibilities were more inclined to adopt innovations in their teaching. The research also revealed that limited resources are a hindrance to fully embracing innovations, but teachers recognized the need to incorporate digital technology and active teaching methods in their instruction. The conclusions indicate that responsibility and innovation among teachers are deeply interconnected, and they have a significant impact on the quality of teaching and student engagement.